Podjetniško izobraževanje ter podjetniška aktivnost v delu Podonavske regije - Tominc, Polona (Pedagoška obzorja, 2013)
In this paper the impact of one's entrepreneurial education and training on starting entrepreneurial activity is analyzed. The research is based on findings suggesting that those having confidence in own skills and ability for entrepreneurship are more likely to start entrepreneurial career, while entrepreneurial education and training is important for increasing this self-efficacy. Three, the most important sources of entrepreneurial education and training are formal education at primary and secondary level, informal training at universities and especially self-studies, through reading books, observing other people in business or by working in someone else's business, which have also the strongest impact on entrepreneurial activity. The curricula especially at the tertiary level should concentrate on those specific knowledge and skills needed by most potential entrepreneurs - regarding our results, this should include especially direct experience in the real business environment.
Keywords: podjetništvo; education; izobraževanje; izobraževalna politika; aktivnosti